2016
DOI: 10.1016/j.brainres.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory oligodendrocyte

Abstract: Oligodendrocytes, the myelinating glial cells of the central nervous system (CNS), are due to their high specialization and metabolic needs highly vulnerable to various insults. This led to a general view that oligodendrocytes are defenseless victims during brain damage such as occurs in acute and chronic CNS inflammation. However, this view is challenged by increasing evidence that oligodendrocytes are capable of expressing a wide range of immunomodulatory molecules. They express various cytokines and chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 97 publications
(103 reference statements)
4
59
0
Order By: Relevance
“…Homeostatic glial activation can beneficial in dealing with minor tissue dysfunction, but it can also become pathogenic if the activation is persistent 20 . Though oligodendrocytes have recently been suggested to participate in immune responses 21 , imaging methods are currently only available for microglia and astrocyte imaging in humans, and thus we will focus on techniques targeting these cells. Future efforts will hopefully lead to cell-specific imaging strategies for all CNS immunocompetent cells.…”
Section: Imaging Resident Immunocompetent Cellsmentioning
confidence: 99%
“…Homeostatic glial activation can beneficial in dealing with minor tissue dysfunction, but it can also become pathogenic if the activation is persistent 20 . Though oligodendrocytes have recently been suggested to participate in immune responses 21 , imaging methods are currently only available for microglia and astrocyte imaging in humans, and thus we will focus on techniques targeting these cells. Future efforts will hopefully lead to cell-specific imaging strategies for all CNS immunocompetent cells.…”
Section: Imaging Resident Immunocompetent Cellsmentioning
confidence: 99%
“…To better define the role of glial cells in ECM development, we further investigated oligodendrocytes, recently recognized as CNS immunomodulatory cells, rather than “defenseless victims” of brain inflammation caused by microglia activation [41], since oligodendrocytes express a wide range of immunomodulatory molecules (reviewed in [42]). Immunofluorescence staining was performed on brain of WT and ST2 -/- infected mice, and compared to naïve mice, to evaluate IL-33 production by oligodendrocyte after Pb A-infection (Fig 6A and 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Microglia, considered as the classical innate immune cells of the CNS, may impact oligodendrocyte function (reviewed in [42]). Indeed, a recent study reported oligodendrocyte damage after IL-1β stimulation in vitro [43].…”
Section: Resultsmentioning
confidence: 99%
“…For example, gliosis may occur independent of evident axonal pathology and vice versa low-grade gliosis is not necessarily detrimental to axons or myelin, as seen in mice lacking the myelin protein tetraspanin-2 (de Monasterio-Schrader et al, 2013). Indeed, immune cells may be modulated by axonal pathology as well as by oligodendroglial molecules (Zeis, Enz, & Schaeren-Wiemers, 2016). On the other hand, we are not aware of in vivo evidence indicating a direct role for activated microglia or astrocytes in enhancing axonal pathology in SPG2/PMD spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%